Communication failure and civil war in Virgil’s Aeneid, Lucan’s Bellum Ciuile and Statius’ Thebaid - Chhibber, Ashley (2023)
This thesis explores the presence and significance of scenes of communication failure in three Latin epics. It argues for a connection between these episodes based on the poems’ shared interest in the experience of civil war, which, as the first chapter establishes, results from the recurrence of civil war throughout the first centuries BCE and CE. Although speech and rhetoric in Latin epic have been examined from a variety of perspectives, there has been no sustained analysis of the connections between the wide range of scenes in which communication seems ineffective.